Analisis Kadar Merkuri (Hg) pada Rambut Pekerja Tambang di Pertambangan Emas Tanpa Ijin (PETI) Kabupaten Parigi Moutong dalam Hubungannya dengan Frekuensi Konsumsi Ikan: Analysis of Mercury (Hg) Levels in Hair of Gold Miners at Ilegal Gold Mining Activities of Parigi Moutong Regency in Relation to Frequency of Fish Consumption - Musafira; Ernawaty Rasul (KOVALEN: Jurnal Riset Kimia, 2022)
Illegal gold mining is a mining activity using traditional methods. Mining activities in the traditional way process mining products using the amalgamation process. In the amalgamation process, gold is bound by adding mercury and the waste from the amalgamation process which may still contain mercury is discharged into the environment. It can have an impact on the accumulation of mercury in humans, especially the miners either directly or through the food chain. This study aims to determine the amount of mercury concentration that has accumulated in miners' hair in relation to the frequency of fish consumption. The sampling method is done by random sampling method in five sub-districts in Parigi Moutong Regency. Fish consumption frequency data was taken by filling out questionnaires by respondents (miners). Analysis of mercury content in hair samples was carried out using the Mercury Analyzer NIC MA-3000. The results showed that the concentration of mercury in miners in all sub-districts exceeded the quality standard set by USEPA, which was above 1 mg/Kg. The highest mercury content was found in the miner's hair in Moutong District which was 3.48 mg/kg, while the lowest mercury content was found in the miner’s hair in Kasimbar District which was 1.06 mg/kg. Based on these results, the gold miners in the five sub-districts have been contaminated with mercury. A correlation value above 0.5 indicates a correlation between fish consumption and mercury concentrations in hair, thereby it can be said that the source of mercury exposure to miners can also come from the fish they consume.